Digital Agency and Counter-Narratives in Religious Mediation: Feminist Niqab-Wearing Women on Instagram @cadargarislucu - Hasyim, Nanang Mizwar; Ghozali, Mahbub (An-Nida', 2026)
This study analyses the mediation practices undertaken by the Instagram community @cadargarislucu in constructing the religious identity of niqab-wearing women within Indonesia’s digital public sphere. Unlike previous studies that focus on representation and identity, this research examines how media-based agency is employed to transform the meaning of religious symbols through digital practices. The study adopts a qualitative approach by analysing 13 Instagram posts, including videos and carousels, using content analysis and critical discourse analysis. The analysis is conducted in two stages: content analysis to identify themes and message patterns, followed by critical discourse analysis to examine how meaning is constructed through the relationship between text, discursive practices, and social context. The analytical framework integrates Stewart M. Hoover’s theory of religious mediation with Norman Fairclough’s critical discourse analysis to explore the interplay between text, discursive practices, and social context. The findings identify four interrelated forms of mediation practices: first, the appropriation of viral language to construct communicative religious-feminist narratives; second, the utilisation of contemporary issues and digital technology as sources of symbolic culture; third, the negotiation of meaning through the articulation of value-based stances; and fourth the hybridisation of religious-feminist identity as a form of reinterpretation of the niqab. These practices demonstrate that digital agency enables the transformation of the niqab’s meaning from a stigmatised symbol into a representation of empowerment, inclusivity, and religious moderation. These findings underscore the central role of community agency in the construction of religious meaning within digital spaces and contribute to the development of counter-narrative strategies employed by minority groups to challenge dominant discourses on social media.